ANALISIS BAURAN PEMASARAN (MARKETING MIX) DALAM MENINGKATKAN VOLUME PENJUALAN (STUDI KASUS PADA KEDAI PIS BURGER PEKANBARU) - Munawaroh, Putri; Othman, Lie (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to analyze the application of the marketing mix to increase sales volume at PIS Burger, a culinary MSME in Pekanbaru City. The research method used was descriptive qualitative. Data collection was conducted through observation, in-depth interviews with the owner, employees, and customers, and documentation. The results show that PIS Burger is able to maintain its existence through consistent product quality and distinctive flavors, affordable pricing, a strategic location, friendly and efficient service, and a simple shop atmosphere that holds historical and emotional value for customers. The promotional strategy implemented is still dominated by word of mouth, which has proven effective in retaining existing customers but has not been optimal in reaching new markets. This study concludes that the marketing mix implemented by PIS Burger has supported increased sales and customer loyalty. However, strengthening digital promotions, menu innovation, and improving physical facilities are needed to sustainably increase business competitiveness. Keywords: Marketing Mix, Sales Volume, PIS Burger